Making solutions for choosing industrial concrete floors and expedience of reliability evaluation - Medelienė, Violeta; Žiogas, Vigantas Antanas (Journal of Civil Engineering and Management, 2010)
The rapid growth of economy and the recent development of industry in Lithuania have considerably increased, and therefore the need for industrial concrete floors also has a tendency to growing. The floor is used in almost all industrial companies because of differently modified concrete and a number of coating materials. It is more difficult to make an effective solution for choosing the required coating due to the supply of many different coating materials, an improvement in technological solutions, stiffening economic and ergonomic requirements. The article focuses on the complex problems of working towards a solution for selecting coating, presents the evaluation of conditions for floor exploitation and analyses mistakes and economic outcomes. The paper describes the expedience and problems of evaluating solutions for choosing floor covering in terms of reliability, makes the complex model of factors that influence reliability and presents a practical example of calculating statistical reliability. First Published Online: 10 Feb 2011